A two-step approach for the seismic assessment of masonry structures accounting for the actual masonry pattern - Szabó, Simon (2023)
Seismic assessment of masonry structures is a pressing concern in the scientific community. Over the last few decades, significant progress has been made in developing numerical modelling strategies for masonry. However, due to the unique mechanics of masonry, which exhibit a quasi-brittle and anisotropic behaviour, there is no trade-off between accuracy and computational efficiency when conducting numerical simulations of masonry structures. This study proposes a new approach to conduct in-plane numerical simulations of masonry structures, which couple limit and pushover analyses considering the actual masonry pattern. The first step of the procedure involves a block-based limit analysis, which considers the actual masonry pattern. Macroblocks, i.e., the portions which compose the collapse mechanism, are then identified using an ad-hoc algorithm that searches for the pivot point of the obtained failure mechanisms. In the second step, a pushover analysis is conducted on the simplified structure composed of macroblocks, considered as continuum bodies, interacting via frictional interfaces. The proposed approach is preliminary tested on two structural-scale benchmarks made of dry-stack masonry, showing promising results.